PENGARUH E-TRUST DAN PROMOSI TERHADAP E-LOYALTY DAN E-SATISFACTION SEBAGAI VARIABEL INTERVENING PADA PENGGUNA OVO DI KELURAHAN SUKARAMAI II KOTA MEDAN - Madeline Angeline; Sharen Imanuel; Apren Halomoan Hutasoit; Suci Pertiwi (Jurnal Ilmiah METHONOMI, 2023)
This research aims to understand and analyze the influence of e-trust and promotion on e-loyalty. The study also aims to determine whether e-satisfaction can act as a mediator between e-trust and promotion on e-loyalty. The research was conducted in the Sukaramai II neighborhood of Medan City, with the subjects being individuals using OVO. This is an associative research with a sample size of 96 respondents. Data collection was done through questionnaires distributed to OVO users. The results of this study indicate that e-trust has a significant influence on e-satisfaction, and promotion also has a significant influence on e-satisfaction. Furthermore, e-trust and promotion have a direct and significant impact on e-loyalty. Additionally, the research findings suggest that e-satisfaction does not act as a mediator between e-trust and promotion on e-loyalty.